STRATEGI KRISIS KOMUNIKASI PT. NIPPON INDOSARI CORPORINDO TBK (SARI ROTI) PADA KASUS #BOIKOTSARIROTI - Mega Mercia Laraswati; Raqhuel Villy Permata Eidelweis; Amanda Pramarta Putri (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
#BoikotSariRoti happened in 2016, December 2nd. It is started when there are some Sari Roti street tradesman give Sari Roti products to symphatizer Aksi 212 freely. #BoikotSariRoti case brings PT. Nippon Indosari Corporindo Tbk. into crisis. To go out from crisis, PT. Nippon Indosari Corporindo Tbk. does some crisis communication strategies. In this research, researchers use qualitative descriptive methode. The researchers also use Situational Crisis Communication Theory (SCCT) to analyze what strategies that they used. This study aims to understand the communication crisis strategy of PT. Nippon Indosari Corporindo Tbk (Sari Roti) in the case of #BoikotSariRoti. The researchers found that #BoikotSariRoti is included in preventable cluster which caused by human error. The responses types to face this crisis diminish spesifically excuse. They also did behavioral intention. From this case, Sari Roti is quite successful when execute their strategy. It can be seen when Sari Roti can increasing their selling and maintain their existance.